Answer:
The ball reached its maximum height of (
) in (
).
Step-by-step explanation:
This question is essentially asking one to find the vertex of the parabola formed by the given equation. One could plot the equation, but it would be far more efficient to complete the square. Completing the square of an equation is a process by which a person converts the equation of a parabola from standard form to vertex form.
The first step in completing the square is to group the quadratic and linear term:
![h(t)=-5t^2 + 10t + 6\\\\h(t) = (-5t^2 + 10t) + 6](https://tex.z-dn.net/?f=h%28t%29%3D-5t%5E2%20%2B%2010t%20%2B%206%5C%5C%5C%5Ch%28t%29%20%3D%20%28-5t%5E2%20%2B%2010t%29%20%2B%206)
Now factor out the coefficient of the quadratic term:
![h(t)=-5(t^2 -2t) + 6](https://tex.z-dn.net/?f=h%28t%29%3D-5%28t%5E2%20-2t%29%20%2B%206)
After doing so, add a constant such that the terms inside the parenthesis form a perfect square, don't forget to balance the equation by adding the inverse of the added constant term:
![h(t) = -5(t^2 -2t) + 6\\\\h(t) = -5(t^2 -2t + 1 -1 ) + 6](https://tex.z-dn.net/?f=h%28t%29%20%3D%20-5%28t%5E2%20-2t%29%20%2B%206%5C%5C%5C%5Ch%28t%29%20%3D%20-5%28t%5E2%20-2t%20%2B%201%20-1%20%29%20%2B%206)
Now take the balancing term out of the parenthesis:
![\\\\h(t)=-5(t^2 -2t + 1) + 6 + ((-1)(-5))](https://tex.z-dn.net/?f=%5C%5C%5C%5Ch%28t%29%3D-5%28t%5E2%20-2t%20%2B%201%29%20%2B%206%20%2B%20%28%28-1%29%28-5%29%29)
Simplify:
![h(t) = -5(t^2 -2t + 1) + 6 + 5\\\\h(t) = -5(t-1)^2 + 11](https://tex.z-dn.net/?f=h%28t%29%20%3D%20-5%28t%5E2%20-2t%20%2B%201%29%20%2B%206%20%2B%205%5C%5C%5C%5Ch%28t%29%20%3D%20-5%28t-1%29%5E2%20%2B%2011)
The x-coordinate of the vertex of the parabola is equal to the additive inverse of the numerical part of the quadratic term. The y-coordinate of the vertex is the constant term outside of the parenthesis. Thus, the vertex of the parabola is:
![(1, 11)](https://tex.z-dn.net/?f=%281%2C%2011%29)
Answer:
9/10 I do this a lot
step-by-step explanation:
1/2 changes to 5/10 and 2/5 becomes 4/10 then you add and there is your answer
It can be a fraction, a decimal, a mixed number, or any irrational number.
Write the left side of the given expression as N/D, where
N = sinA - sin3A + sin5A - sin7A
D = cosA - cos3A - cos5A + cos7A
Therefore we want to show that N/D = cot2A.
We shall use these identities:
sin x - sin y = 2cos((x+y)/2)*sin((x-y)/2)
cos x - cos y = -2sin((x+y)/2)*sin((x-y)2)
N = -(sin7A - sinA) + sin5A - sin3A
= -2cos4A*sin3A + 2cos4A*sinA
= 2cos4A(sinA - sin3A)
= 2cos4A*2cos(2A)sin(-A)
= -4cos4A*cos2A*sinA
D = cos7A + cosA - (cos5A + cos3A)
= 2cos4A*cos3A - 2cos4A*cosA
= 2cos4A(cos3A - cosA)
= 2cos4A*(-2)sin2A*sinA
= -4cos4A*sin2A*sinA
Therefore
N/D = [-4cos4A*cos2A*sinA]/[-4cos4A*sin2A*sinA]
= cos2A/sin2A
= cot2A
This verifies the identity.